Behavior prediction requires implicit measures of stimulus‐goal discrepancies and expected utilities of behavior options rather than of attitudes toward objects. Issue 5 (1st July 2022) - Moors, Agnes; Köster, Massimo
Abstract: Meta‐analyses show low correlations between implicit attitude measures and behavior measures, suggesting that these attitude measures are weak predictors of behavior. Researchers of implicit cognition have resorted to several rescue strategies. Their most important reply, based on a traditional dual‐process theory of behavior causation, is that attitudes toward objects (positive/negative) automatically activate specific action tendencies (approach/avoidance), but that this stimulus‐driven process can be overruled by a nonautomatic goal‐directed process in which the expected utilities of action options are weighed up. According to such a theory, it makes sense to continue measuring attitudes with implicit measures, but research should also take into account the moderating role of goals and other factors. We propose an alternative dual‐process theory in which goal‐directed processes can also be automatic and count as the most important cause of behavior. According to this theory, the goal‐directed process responsible for action selection is further preceded by the detection of a stimulus‐goal discrepancy. Based on this alternative theory, we propose to no longer measure attitudes toward objects but rather to measure (a) the magnitude of stimulus‐goal discrepancies as well as (b) the expected utility of the behavior at stake, understood as the product of the values of the outcomes of the behavior, and the behavior‐outcome expectancies. Here too, implicit measures are needed because people may not always have conscious access to these constructs or be motivated to disclose them. This article is categorized under: Psychology > Theory and Methods Psychology > Emotion and Motivation Psychology > Reasoning and Decision Making Abstract : What should implicit measures measure? According to the traditional (stimulus‐driven) approach to behavior causation, implicit measures should measure the valence of stimuli or the attitude towards objects. According to the alternative (goal‐directed) approach to behavior causation, implicit measures should measure (a) the magnitude of stimulus‐goal discrepancies as well as (b) the expected utility of the behavior at stake, understood as the product of the values of the outcomes of the behavior, and the behavior‐outcome expectancies.